Facile hydrothermal synthesis of novel Cu2O core-shell nanospheres via a template-free route - Zhang, Huijuan (2013)
Novel cuprous oxide Cu2O core-shell nanospheres with diameter around 445 nm have been successfully fabricated by a facile, one-pot and template-free route. The synthesis of these nanospheres is accomplished through a hydrothermal reaction of cupric acetate with o-anisidine as the reducing agent. Based on the structural and compositional evolution, the process mechanism was proposed to initiate with the formation of intermediate non-crystalline nanospheres. Subsequent reductive conversion of these intermediates to CuO/Cu2O nanocrystallite aggregates is followed by a spontaneous hollowing process in which core-shell nanospheres form by inside-out Ostwald ripening. The phase purity of the Cu2O can be improved by prolonging the aging time or increasing the starting concentration of o-anisidine. These Cu2O nanospheres have an absorption band within the visible range with a peak at 470 nm and may be potentially applicable for solar energy conversion.